An investigation of pyrolysis kinetics in microwave-assisted conversion of oil palm shell and activated carbon for sustainable bio-oil production - Jumrat, Saysunee; Punvichai, Teerasak; Sae-jie, Wichuta; Boonsawaeng, Watsana; Klaiklay, Saranyoo; Muangprathub, Jirapond; Karrila, Seppo; Pianoroj, Yutthapong (Engineering and Applied Science Research, 2024)
This study explores microwave (MW) pyrolysis of oil palm shell (OPS) blended with activated carbon (AC) to produce bio-oil, focusing on the pyrolysis kinetics and the effect of different feedstock ratios. Three OPS mixtures (70:30, 75:25, and 80:20) were analyzed at a constant temperature of 400°C. Gas chromatography-mass spectrometry (GC-MS) revealed that acetic acid, phenol, and other oxygenated compounds were dominant in the resulting bio-oils. Pyrolysis kinetics were modeled using a first-order reaction approach, with rate constants and activation energies determined for each blend. The 75:25 ratio yielded the highest bio-oil content and exhibited the most favorable kinetic performance, showing strong alignment between experimental and simulated data (R² = 0.758). The study also examined the impact of pyrolysis temperatures (400°C, 500°C, and 600°C) at the fixed 75:25 ratio, demonstrating that temperature plays a key role in both enhancing bio-oil yield and altering its chemical composition.